Triple Nexus Analysis: A Case Study of UNICEF and ECW Collaboration in Emergency Education Intervention in Haiti - A’yunina, Qurrota (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
Triple nexus is a concept consisting of three main elements: humanity, development, and peace. One example of the integration of the triple nexus concept is in the case study of emergency education intervention for children victims of the internal crisis in Haiti. Before the crisis occurred, Haiti was already the poorest country in the Western Hemisphere. This condition was exacerbated by the presence of armed groups that terrorized citizens and internal political chaos, resulting in poor living conditions for the people there, especially children. Seeing this, this study aims to analyze how the integration of the triple nexus concept in the cooperation of the United Nations Children's Fund (UNICEF) and several related partners such as Education Cannot Wait (ECW) in emergency education interventions in Haiti. Previous studies have discussed UNICEF's work programs in different conceptual frameworks, this study tends to focus on the triple nexus concept in UNICEF's collaborative actions carried out together with partners. This paper uses a qualitative research method with a relevant secondary data base collected from previous sources such as articles, news, and academic publications. This paper finds that humanity, development and peace conceptualized in these three relationships are successfully reflected in the educational intervention efforts in Haiti by UNICEF in collaboration with EWC as a donor